FILOSOFI TRADISI NGELOANG CAPAH DI PURA DESA/BALE AGUNG DESA TAMBLANG KECAMATAN KUBUTAMBAHAN KABUPATEN BULELENG (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
Ngeloang Capah tradition is a tradition that is carried out from generation to generation thatreflects a community belief and its implementation coincides with the Purnama Kedasa monthonce a year. The purpose of this study is to reveal the basis of the Ngeloang Capah traditionalong with the philosophical values contained therein. This study uses a qualitative approachwith interview, observation and documentation methods conducted in Tamblang Village. Theresults of the study indicate that the Ngeloang Capah tradition is an important part of the livesof the Tamblang Village community, the sacredness of this tradition is because there are mythsthat develop in the community and strong beliefs of the Tamblang Village community. In itsimplementation, the banten capah is used as a medium which is manifested in the yajñaceremony. The essence of the Ngeloang Capah tradition can be seen from the value of harmonyreflected in the Tri Hita Karana teachings, harmony between humans and God as amanifestation of spirituality, harmony between humans and others such as the establishmentof togetherness and good communication between each other and harmony with theenvironment in the form of environmental preservation. Ethical values that refer to moralbehavioral norms that are upheld by society in establishing social and religious life. The valueof cultural preservation is also one of the things that can be done by the Tamblang Villagecommunity by continuing to carry out traditions sustainably.
Keywords: philosophy, ngeloang capah tradition